The Effect Of Ownership Structure On The Performance Of Intellectual Capital - Astian Yosi Meilani; Siti Nur Azizah; Hadi Pramono; Bima Cinintya Pratama (Jurnal Akademi Akuntansi, 2021)
This study aims to show empirical evidence of the effect of managerial ownership, institutional ownership, foreign ownership and government ownership on intellectual capital performance as the dependent variable. This study relates the influence between these variables by expanding the concept and understanding of Resource-Based Theory, Agency Theory and Stakeholder Theory. The sample in this study is the mining sector companies listed on the Indonesia Stock Exchange in 2016-2019 using purposive sampling technique, namely selecting samples with certain criteria to get more valid results. The data analysis technique used is the classical assumption test, then the results are analyzed using multiple regression analysis to prove the influence between variables by utilizing an accurate SPSS application. The results of this study indicate that institutional ownership and foreign ownership have a positive effect on intellectual capital performance in mining companies, while managerial ownership and government ownership do not show any effect on intellectual capital performance in mining companies in Indonesia. This research contributes to the theory and practice of companies in the conduct of business. However, this study has not been able to prove the influence of managerial and government ownership on intellectual capital performance, so that further research can consider other corporate sectors whose managerial and government ownership is quite dominant.